„Wiadomości Skautowe”. Establishment – editing – characteristics - Guzewicz, Wojciech; Szymańska, Magdalena (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
The article presents the creation, editing, profile and graphic design of „Wiadomości Skautowe” in 1916, the periodical of the Polish Scout Organization - one of the largest Scouting Organizations Operating in Poland during the First World War. It is based mainly on articles published in 18 issues of this magazine.